Luminescent, redox-active diphenothiazine dumbbells expanded by conjugated arenes and heteroarenes - Hauck, Martina; Turdean, Raluca; Memminger, Karin; Schönhaber, Jan; Rominger, Frank; Müller, T. J. J. (The journal of organic chemistry, 2010)
Dumbbell-shaped diphenothiazines bridged by conjugatively linked (hetero)aromatic moieties were synthesized in a modular fashion by Suzuki−Miyaura coupling in good yields. The electronic structure was studied by DFT computations, determining the geometry optimized lowest energy conformers and scrutinizing the Kohn−Sham FMOs. The torsional deviation from coplanarity is predominantly influencing the electronic structure, i.e., by deviation from ideal overlap and maximal electron transmission. The reversible oxidation potentials assigned to the phenothiazinyl electrophores in most cases can thereby be qualitatively rationalized. All dumbbell-shaped diphenothiazines are strongly luminescent, which can be attributed to extended π-electron conjugation with considerable excited state electronic coupling as a consequence of large structural and electronic distributional changes upon photoexcitation.
Gesehen am 27.03.2023